Direct oral anti-Xa anticoagulants versus warfarin in newly diagnosed atrial fibrillation and CKD: the Korean National Health Insurance Data - Kee, Youn Kyung; Jeon, Hee Jung; Oh, Jieun; Yoo, Tae-Hyun; Kang, Dongwoo; Lee, Jungkuk; Shin, Dong Ho (Frontiers in Medicine, 2023)
Despite the benefits of direct oral anti-Xa anticoagulants (DOACs), whether DOAC therapy has a better risk-benefit profile than warfarin therapy in patients with non-valvular atrial fibrillation (AF) and chronic kidney disease (CKD), including end-stage renal disease (ESRD), remains uncertain. Using a nationwide database, we conducted a retrospective study to investigate the effectiveness and safety of DOACs compared to warfarin in these patients. We evaluated patients with incident non-valvular AF and CKD in the Korea National Health Insurance Database from 2013 to 2018. The primary and secondary effectiveness outcomes were ischemic stroke and all-cause mortality. The primary safety outcomes included intracranial hemorrhage, gastrointestinal bleeding, and extracranial or unclassified major bleeding. Among the 1,885 patients, 970 (51.5%) initiated warfarin therapy, whereas 915 (48.5%) initiated DOAC therapy. Although DOAC users had a lower proportion of patients with ESRD than warfarin users (6.6% vs. 32.5%, p <0.001), DOAC users had a higher Charlson comorbidity index, CHA2DS2-VASC score, and modified HAS-BLED score compared with warfarin users. During a mean follow-up period of 23.8 months, there were 293 and 214 cases of ischemic stroke and all-cause death, respectively. There was no difference in ischemic stroke between the two groups. However, Kaplan-Meier survival analysis showed that all-cause mortality was significantly lower in DOAC users than in warfarin users. In multivariate Cox regression analyses, the hazard ratio for all-cause mortality compared to warfarin therapy was 0.41 (95% CI, 0.30-0.56; p < 0.001) in DOAC therapy. Additionally, DOAC therapy significantly reduced intracranial hemorrhage and gastrointestinal bleeding in multivariate Cox regression analyses. This study showed that DOAC therapy had a better risk-benefit profile than warfarin therapy in patients with AF and CKD. To clarify the benefits of DOACs in patients with AF and CKD, further well-designed clinical trials are needed.